CHARACTERISATION PHYSICAL CHEMISTRY OF BIODIESEL OF PEQUI (Caryocar brasiliensis) - BATISTA, A. C.F.; VIEIRA, A. T.; RODRIGUES, H. S.; BORGES, K. A.; REZENDE, H. P.; PORTELA, F. M.; CHIALASTRI, R. A.; HERNANDEZ –TERRONES, M. G. (Revista Brasileira de Engenharia de Biossistemas, 2013)
The Pequi, the family tree of cariocáceas can also be found throughout the region Central West (considered the capital of fruit) and in the states of Rondônia (the east), Minas Gerais (north and west), Pará (southwest), Tocantins, Maranhão (southern end), Piauí (southern end), Bahia (west) and Ceará(South). The pequi (Caryocar brasiliensis Camb) Is a native fruit widely disseminated in Brazil (central region). Its fruits are edible and used for extraction of oil, consisting of triglycerides that can be used in the production of biodiesel. This biofuel to be used in engines should be within the specifications required by the Agency National Petroleum, Natural Gas and Biofuels (NPA). This requires making several tests that can certify its quality. It is proposed that work on physical and chemical characteristics of biodiesel, methanol and ethyl pequi. The physical and chemical testing of biodiesel, methanol and ethyl oil pequi were conducted under the rules of the American Society for Testing and Materials "American Society for Testing and material" (ASTM)